THE MAIN CRITERIA OF GENDER LINGUISTICS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
In present level gender linguistics is appeared as one of developing direction to learn language more deeply and to analyze the reflection of gender in it. The study of men and women representation accesses us to identify language mechanisms that express gender relations and realize the matter happening in language and society.Phraseology represents as retranslation of culture and appears as successful source to research the relations between genders. This system includes stereotypical behavior and perception of men and women for representators of opposite genders.